From the 1960s to the Present: Chilean Elites and the Tensions of Neoliberal Education - Retamal-Salazar, J (Springer Science and Business Media B.V., 2025)
The chapter examines the profound influence wielded by Chilean political and economic elites over Chile’s education system in the context of neoliberalism. Since the 1960s, these elites have strategically navigated the socio-political Chilean landscape, promoting the privatization and standardization of education, often exacerbating social tensions. Their quest for a “Nobility State” has driven them to seek symbolic recognition through national education prizes, thereby entrenching a closed and insular elite. Despite the authoritarian backdrop of the 1970s and 1980s, which saw the rise of US-trained technocrats and the consolidation of a neoliberal education system, the return to democracy in the 1990s ushered in reforms aimed at social equality, influenced by the “Third Way” ideology. The 2000s further reconfigured the educational landscape with accountability and evidence-based policies. Throughout these decades, the elites have maintained their dominance, often at the expense of grassroots movements and local needs, perpetuating a complex interplay of power and influence among diverse elite groups that continues to shape the Chilean education system today. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2025.